Methods of the 7th National Audit Project (NAP7) of the Royal College of Anaesthetists: peri‐operative cardiac arrest. (16th September 2022) - Kane, A. D.; Armstrong, R. A.; Kursumovic, E.; Cook, T. M.; Oglesby, F. C.; Cortes, L.; Moppett, I. K.; Moonesinghe, S. R.; Agarwal, S.; Bouch, D. C.; Cordingley, J.; Davies, M. T.; et al.
Summary: Cardiac arrest in the peri‐operative period is rare but associated with significant morbidity and mortality. Current reporting systems do not capture many such events, so there is an incomplete understanding of incidence and outcomes. As peri‐operative cardiac arrest is rare, many hospitals may only see a small number of cases over long periods, and anaesthetists may not be involved in such cases for years. Therefore, a large‐scale prospective cohort is needed to gain a deep understanding of events leading up to cardiac arrest, management of the arrest itself and patient outcomes. Consequently, the Royal College of Anaesthetists chose peri‐operative cardiac arrest as the 7th National Audit Project topic. The study was open to all UK hospitals offering anaesthetic services and had a three‐part design. First, baseline surveys of all anaesthetic departments and anaesthetists in the UK, examining respondents' prior peri‐operative cardiac arrest experience, resuscitation training and local departmental preparedness. Second, an activity survey to record anonymised details of all anaesthetic activity in each site over 4 days, enabling national estimates of annual anaesthetic activity, complexity and complication rates. Third, a case registry of all instances of peri‐operative cardiac arrest in the UK, reported confidentially and anonymously, over 1 year starting 16 June 2021, followed by expert review using a structured process to minimise bias. The definition of peri‐operative cardiac arrest was the delivery of five or more chest compressions and/or defibrillation in a patient having a procedure under the care of an anaesthetist. The peri‐operative period began with the World Health Organization 'sign‐in' checklist or first hands‐on contact with the patient and ended either 24 h after the patient handover (e.g. to the recovery room or intensive care unit) or at discharge if this occured earlier than 24 h. These components described the epidemiology of peri‐operative cardiac arrest in the UK and provide a basis for developing guidelines and interventional studies.